Improving polytechnic students’ high-order-thinking-skills through inquiry-based learning in mathematics classroom - Muhammad Sani Abdurrahman; Abdullah Abdul Halim; Osman Sharifah (Institute of Advanced Engineering and Science, 2021)
Mathematics is one of the most emphasized subjects and has grown immensely to provide a strong base for programs in science, engineering and technology. Training students in this field will give them the opportunity to improve their high order thinking skills (HOTS). But the students’ HOTS level is at low stage due to the learning approaches employed in classrooms. As a result, the study aimed at looking into the effect of inquiry-based learning (IBL) in improving polytechnic students’ level of HOTS. Quasi-experimental design was used in this study involving two sampled National Diploma II classes. There were 73 students participated in this study (36 students for experimental group and 37 students for control group). HOTS questions and worksheets based on IBL are the instruments used for this study. At the α=0.05 (p=0.000) level of significance, the results of the independent-sample t-test revealed a significant difference between the mean post-test scores of the experimental group and the control group. Moreover, the students’ overall HOTS level was discovered to be (applying, analyzing, evaluating, and creating) improving through this approach. In conclusion, IBL can have a positive effect on the HOTS of polytechnic students in mathematics classroom.